Vers une théorie du système monétaire international - Woehrling, Francis (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The idea of an international monetary System comprised of a number of countries (monetary zones) linked together by an exchange rate mechanism controlled by the I.M.F. - the system's center - is the basis of the vast majority of the analyses and reform schemes respecting the System.This idea does not correspond to international economic and monetary reality which is organized around one or several international currencies (or key currencies) with regard to which the Central Bank(s) exercise(s) the de facto role of the System's monetary authority. This fact raises two theoretical questions : How is a Central Bank led to exercise such a role ? How, in fact, does the System function ?It is significant that the textbooks rarely treat the first question other than from an historical perspective. It would nevertheless appear that the explanation for the development of Euromarkefs employs a number of analytical tools that allow for a theoretical framework for the evolution of the I.M.S. based on the idea of competition among financial institutions and banks.On the one hand, this theory anticipates the long-term integration process of markets characterized by the erosion of regional markets and the growth of a new dominant market and therefore by the coexistence of regional authorities and a central authority sharing monetary power. On the other, it advocates the mix of unification and macroeconomic management policies that these authorities must adhere to in order to optimize the process.In the second part of the text the operation of a monetary zone such as the dollar standard of the last thirty years is examined. The organization of that zone provides an example of the distribution of monetary power as between the Federal Reserve System and the central banks of other countries. A consideration of the operation of an International Monetary System having two key currencies completes the study.